The Role of Gender in Patients with Borderline Personality Disorder: Differences Related to Hopelessness, Alexithymia, Coping Strategies, and Sensory Profile - Andrea Amerio; Antimo Natale; Giovanni Battista Gnecco; Alessio Lechiara; Edoardo Verrina; Davide Bianchi; Laura Fusar-Poli; Alessandra Costanza; Gianluca Serafini; Mario Amore; Andrea Aguglia (Medicina, 2023)
Background and Objectives: Gender differences are poorly investigated in patients with borderline personality disorder (BPD), although they could be useful in determining the most appropriate pharmacological and non-pharmacological treatment. The aim of the present study was to compare sociodemographic and clinical characteristics and the emotional and behavioral dimensions (such as coping, alexithymia, and sensory profile) between males and females with BPD. Material and Methods: Two hundred seven participants were recruited. Sociodemographic and clinical variables were collected through a self-administered questionnaire. The Adolescent/Adult Sensory Profile (AASP), Beck Hopelessness Scale (BHS), Coping Orientation to Problems Experienced (COPE), and Toronto Alexithymia Scale (TAS-20) were administered. Results: Male patients with BPD showed more involuntary hospitalizations and greater use of alcohol and illicit substances compared to females. Conversely, females with BPD reported more frequent medication abuse than males. Furthermore, females had high levels of alexithymia and hopelessness. Regarding coping strategies, females with BPD reported higher levels of “restraint coping” and “use of instrumental social support” at COPE. Finally, females with BPD had higher scores in the Sensory Sensitivity and Sensation Avoiding categories at the AASP. Conclusions: Our study highlights gender differences in substance use, emotion expression, future vision, sensory perception, and coping strategies in patients with BPD. Further gender studies may clarify these differences and guide the development of specific and differential treatments in males and females with BPD.